Implementation of the Al-Taisīr Concept in Jamak Prayer for Medical Personnel Performing Surgical Operations - Hafizah, Afiah; Wahid Haddade, Abdul; Shuhufi, Muhammad (Pascasarjana UIN Alauddin Makassar, 2024)
Islamic law is based on strong and flexible principles that are suitable for every country, people, time, and era. There are three principles in Islamic law. First, it is not burdensome and removes difficulties. Second, maintaining the benefit of all human beings. The third is the comprehensive realization of justice. There are many forms of eliminating hardship and difficulty. Among them are in the aspect of worship, in the realm of muamalah and uqūbah (sanctions). In the aspect of worship, for example, the permissibility of qasar prayer, tayamum and iftar for travelers and sick people. A situation that is also related to this is the condition of medical personnel when performing surgical operations that require a short time to carry out. It is not uncommon for this to coincide with the time of prayer until it is close to the time limit. Sometimes, the surgery goes beyond the set prayer time, even entering the next prayer time. This research was conducted using a theological-normative approach or shar'ī approach presented qualitatively. Primary data sources come from verses of the Qur'an, the Prophet's hadith. Secondary data is obtained from various sources, namely literature that studies the concept of al-taisīr, scientific journal articles, print and online media. The data are analyzed by deductive method.